2006
DOI: 10.1111/j.1601-0825.2006.01235.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral lesions in 13‐ to 16‐year‐old students in Duzce, Turkey

Abstract: This study is the first epidemiologic study of oral mucosal lesions in adolescents in Turkey. Angular cheilitis was the only oral mucosal lesion that had a significant correlation with anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
5
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 31 publications
3
43
5
5
Order By: Relevance
“…Several studies have been conducted with population-based samples [1][2][3][4][5]8 and these will probably show different results when compared to studies conducted at universities and centers of specialized health care, with individuals searching for assistance (convenience samples) 6,[9][10][11][12][13] . Studies conducted in dental schools, both with patients in routine dental treatment or referred for stomatological evaluation, in spite of probably showing a different picture from the general population, may better represent a model of what occurs in daily practice of the profession 6,[11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have been conducted with population-based samples [1][2][3][4][5]8 and these will probably show different results when compared to studies conducted at universities and centers of specialized health care, with individuals searching for assistance (convenience samples) 6,[9][10][11][12][13] . Studies conducted in dental schools, both with patients in routine dental treatment or referred for stomatological evaluation, in spite of probably showing a different picture from the general population, may better represent a model of what occurs in daily practice of the profession 6,[11][12][13][14] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies selecting populations by age group provide highly specific information, therefore, need to be analyzed separately. Studies conducted on samples composed of adults and elderly patients, for example, show a higher frequency of denture-related disorders, tobacco-related disorders and chronic traumatic conditions 5,8,14,[17][18][19] , while studies using samples derived from children and adolescent groups show a higher frequency of developmental defects, such as geographic tongue, and physical injuries, such as biting and traumatic ulcers of the mucosa, recurrent aphthous stomatitis and infections, such as candidosis and herpetic lesions 4,10,13,20 . The group of diseases considered by each study also directly influence the frequencies reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Earlier epidemiologic studies of the oral health status of the general population in Turkey focused on specific topics such as lesions related to mucosa, tongue, dentition or bone seperately. 3,4,[6][7][8][9][10][11] The aim of this study was to evaluate the general oral health status, by assessing the prevalence and types of mucosal, tongue, dental and jaw lesions, in a group of patients. This information will serve as a baseline for future studies and could be useful not only in dentistry but also for family medicine and primary care education protocols to improve oral health status in this country.…”
Section: Introductionmentioning
confidence: 99%